2015
DOI: 10.1002/admi.201500097
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin and Switchable Nanoporous Catalytic Membranes of Polystyrene‐b‐poly‐4‐Vinyl Pyridine Block Copolymer Spherical Micelles

Abstract: membranes with a thick separation layer have broad pore size distribution, and this result in poor cutoff properties, fi ltrate loss within the membranes, and low permeation rates. The challenge is to control the pore size precisely at a few nanometers. For increased nanofi ltration performance with higher throughput at lower applied pressure, reduction of the fi lter thickness is benefi cial. [4][5][6][7] However, reaching the limit of a few nanometers is diffi cult when mechanical robustness and tightly cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…For 50-nm-thick nanomembrane, the surface porosity is also useful that was further estimated as 3.2% by using the Hagen-Poiseuille equation (Equation 4 in Methods), since this equation has been widely applied to the filtration membranes with flow channels larger than 2 nm in diameter 22 . An interfacial channel surrounded by three such oligomers with a diameter ~20 nm could be geometrically calculated to have a size of 3.1 nm 31 (Fig. 1e).…”
Section: Resultsmentioning
confidence: 99%
“…For 50-nm-thick nanomembrane, the surface porosity is also useful that was further estimated as 3.2% by using the Hagen-Poiseuille equation (Equation 4 in Methods), since this equation has been widely applied to the filtration membranes with flow channels larger than 2 nm in diameter 22 . An interfacial channel surrounded by three such oligomers with a diameter ~20 nm could be geometrically calculated to have a size of 3.1 nm 31 (Fig. 1e).…”
Section: Resultsmentioning
confidence: 99%
“…Due to common commercial use of Congo red as a colorant in dyeing industry, the research of its degradation is necessary 37 , 38 . Herein honeycomb films decorated with Au nanoparticles were used to photocatalytic degradation of Congo red dye.…”
Section: Resultsmentioning
confidence: 99%
“…Pienamann et al reported that gold nanoparticle immobilized in polystyrene-b-poly vinyl pyridine (PS-P4VP) block copolymer hollow fiber membrane could reduce $80% of PNP feed containing a 100 mL portion of a solution containing 1.39 mg PNP and 37.83 mg NaBH 4 at 0.003 mL/(cm 2 s) flux [28]. In a similar approach we also reported PS-P4VP micelle membranes with gold nanoparticles, which can reduce more than 95% PNP (1.7 mL of water, 0.3 mL of 2 mM solution of PNP, and 1 mL of 0.03 M NaBH4 solution at $200 L m À2 h À1 flux) and 98% Congo red (40 ppm feed at 589.3 L m À2 h À1 flux) in flow reactor [29]. Bruening et al…”
Section: Dye Degradationmentioning
confidence: 64%